STRENGTH OF REINFORCED CONCRETE IN BENDING ELEMENTS CALCULATIONS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The concept of the design strength of reinforced concrete in bending elements is proposed. This concept can be considered a generalized description of concrete. Such approach makes it possible to consider not only the separate strength of concrete and reinforcement, but also their interaction. The design strength of reinforced concrete is determined by ratio of force, which causes destruction of the standard reinforced concrete specimen, to the corresponding geometric characteristic. It was found that using the introduced concept the calculation of reinforced concrete elements can be reduced to well-known formulas of the strength of materials. It is based on generally accepted hypothesis and stress-strain diagrams of materials. The engineering method is developed, which allows to calculate the strength of the bending reinforced concrete elements of rectangular and circular cross-sections equally simple.
Keywords: design strength of reinforced concrete; bending; beam